Urdu Translation and Cross-Cultural Validation of Short Fall Efficacy Scale International - Sajal Amir, Ahsan Hanif, Hafiza Rabia Javed, Fatima Tariq, Amna Buhari, Warda Shafique, Naila Yasmin, Saimoon Rafi, Hira Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In 2008 a tool named Short Fall efficacy international (Short FES-I) was developed by kampen et al to assess fear of fall in older adult’s Short fall efficacy scale was consisted on seven items. It is four points Likert scale. The total score is 28 which shows the high concern of fall and 7 score shows the minimum concern of fall. Objective: The Aim of the study was to translate and validate short fall efficacy scale international in Urdu language. Methods: it was a descriptive cross-sectional study. The study was completed in 2 phases in first phase forward and backward translation process was performed according to proFaNE guidelines. Secondly, the psychometric properties of Urdu version short FES-I were statistically analyzed using a sample of 110 community dwelling older adults at 2 Private hospitals of Shahdara Lahore. Participants completed the Urdu versions of Short FES-I and ABC scale. They also performed TUG. Reliability and validity of short FES-I Urdu version was evaluated by calculating Cronbach’s alpha, intra-class correlation co-efficient and Pearson/ Spearman rank correlation co-efficient. SPSS 21 was used for data analysis. Results: Content validity analyzed by content validity index ranged from (0.92- 1). Reliability and validity of Urdu Version Short FES-I was evaluated by calculating Cronbach’s alpha (α=0.93), intra-class correlation co-efficient (ICC=0.96) and Pearson rank correlation co-efficient (p= -0.90) Short FES-I to ABC scale and to TUG scale its (P=0.82). SPSS 25 was used for data analysis. Conclusion: Urdu version of Short FES-I was designed, tested for its validity and reliability on older adults. Urdu version was linguistically accurate and acceptable. It showed good content, and convergent validity. It also presented high internal consistency and test retest reliability. As an outcome, the Urdu version of short FES-I can be useful for Urdu speaking population. Keywords: Fear of fall, fall efficacy, Urdu version, Reliability, Validity